Measuring The Level Of Strategic Thinking: An Analytical Research In The National Security Advisory - Muhammad Yahya Shamakhi*,; Mahdi Saleh, Khalid (Journal of Economics and Administrative Sciences, 2024)
The current research derives its significance from its focus on the vital subject of strategic thinking. This topic has attracted the attention of researchers and managers alike, as well as the importance of the researched organization, the National Security Advisory, due to its strategic role in maintaining the country's security and stability. The research problem arises from neglecting the role of strategic thinking in the organization's success. The research aims to identify the level of incorporation of strategic thinking within the National Security Adviser, across its four dimensions. The research included a sample of (90) employees at all administrative levels in the National Security Advisory in a narrative analytical mythology.  The questionnaire was the main tool for collecting data and information related to the respondents, and a number of statistical methods were used to obtain results through the SPSS program. The research reached a set of conclusions, the most prominent of which is the disparity in the embodiment levels of strategic thinking in the researched organization, as systems thinking came at the first level, followed by thinking in time, then intentional thinking and finally opportunistic thinking.